Critical Pedagogy in Islamic History Education: Applying Henry Giroux's Framework - Alwy Ahmed Mohamed; Zaki Afifi; Mahmudulhassan Mahmudulhassan (Bulletin of Islamic Research, 2025)
The objective of this research is to explore how Henry Giroux’s theory of critical pedagogy can be applied to Islamic history education in order to enhance critical thinking, social awareness, and transformative learning. The study adopts Giroux’s theoretical framework, which includes ontological, epistemological, and axiological dimensions emphasizing student agency, dialogical learning, and ethical engagement. Using a qualitative literature study as the research method, this paper analyzes scholarly works on critical pedagogy and Islamic education to construct a contextual learning model for undergraduate Islamic history courses. The results demonstrate that traditional approaches to Islamic history often emphasize memorization over critical engagement, thereby limiting students' ability to relate historical narratives to contemporary social realities. By applying Giroux’s critical pedagogy, the study proposes a learning design that includes material and strategy innovations, diverse media tools, and formative assessments focused on critical dialogue and social relevance. The implications of this research suggest that adopting critical pedagogy in Islamic history education can contribute to the development of socially conscious, ethically responsible, and critically aware learners. The originality of this work lies in bridging Western critical pedagogy with Islamic educational objectives, offering a novel curriculum design that aligns with both transformative learning principles and the moral mission of Islamic education